Effect of Temperature and Time on the Sterilization Process of Soft-boned Milkfish - Ahmad Tafsirul Hakim Nur Sya'bani; Musyono, Ari Dwi Nur Indriawan (Jurnal Inovasi Mesin, 2024)
The objectives of this research are: 1) Analyzing the effect of sterilization temperature and time on protein content in soft spiny milkfish, 2) Analyzing the effect of sterilization temperature and time on the bacterial content in soft spiny milkfish, and 3) Knowing the ideal temperature and time in the milkfish sterilization process soft spines. There are various types of diversification of processed milkfish, including processing it into presto milkfish. The shelf life of pressure-cooked milkfish can be increased by sterilization using a high-pressure pressure cooker using a retort tool. In this study, the sterilization process used a combination of temperatures of 110°C, 121°C, 130°C, and times of 10, 20, and 30 minutes. The research method uses an experimental approach. The research location is CV Sekar Tekno, Semarang. The data collection technique uses observation, which is carried out by systematically observing and recording the symptoms being investigated. Data analysis techniques use descriptive statistics and analysis of variance/ANOVA. The results of the research showed that the effect of temperature and time on the sterilization process of soft spiny milkfish did not have a significant effect on the protein content of soft spiny milkfish. Although the protein content of soft spiny milkfish experienced changes up and down during the sterilization process, the protein content did not decrease significantly. The effect of high temperature in the sterilization process of soft spiny milkfish has a significant effect on the number of bacteria present in soft spiny milkfish after the sterilization process. This is indicated by the phenomenon of a constant decrease/value of bacterial content as shown in the following data: temperature 110°C is 148.44 CFU/g, temperature 121°C is 86.78 CFU/g, and temperature 130°C is 25.44 CFU/g. On the other hand, the effect of long sterilization time on the bacterial content of soft spiny milkfish tends to show an up-and-down phenomenon. This is indicated by an increasing trend in the number of bacteria at 30 minutes, which was 125 CFU/g. This phenomenon is caused by a leak in the retort pack used for soft spiny milkfish and other causes that are not yet known for certain in this process. Based on the results of the effect of temperature and time on protein levels and bacterial content, it shows that a temperature of 130°C has a high protein content of 16.6% with the lowest bacterial content, namely 45 CFU/g. At 20 minutes, it had a high protein content of 14.296% with the lowest bacterial content, namely 32.67 CFU/g. So the ideal temperature and time for the sterilization process of soft spiny milkfish is 130°C and 20 minutes